Behavior of the Anaerobic Treatment of Tannery Wastewater at Different Initial Ph Values and Sulfate Concentrations - Huilinir-Curio, C; Montalvo-Martinez, S (2013)
The influence of initial pH and sulfate concentration on the anaerobic digestion of tannery wastewater was studied using the specific methanogenic activity (SMA) test. The SMA tests were performed with a chemical oxygen demand (COD) concentration of 6.5 g/L and SO-2 4 concentrations of 1.95, 3.90, 6.50, 8.45 and 10.4 g/L. The effect of pH was studied at pH 6.8; 6.4 and 6.1. It was found that methane production took place under all conditions, but the use of SO-2 4 concentrations higher than 8.45 g/L and initial pH levels lower than 6.4 caused a decrease of up to 73% of methane production. The influence of pH was significant only for SO -2 4 concentrations lower than 8.45 g/L, with up to 50% inhibition. Specific methanogenic activity for COD/SO-2 4 ratios lower than 0.77 depends basically on this ratio and not on the initial pH value under the conditions of the study. © 2013 Copyright Taylor and Francis Group, LLC.